2022
DOI: 10.4236/jss.2022.107001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Purchasing Behavior of Mobile Phone Consumers: Evidence from Bangladesh

Abstract: An increase in using mobile phones and the availability of many phone brands induced the customers to consider various preferences in purchasing decisions. This descriptive study aimed to determine the factors that affect customers' preferences to buy a cellular phone. The primary data was collected from a survey among the smartphone users in different age groups through a structured questionnaire. The study results show that more than 70 percent of smartphone users belong to the age group under 40 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Evaluasi individu terhadap barang dan pilihan yang dianggap paling menguntungkan dalam hal kualitas, biaya, dan keuntungan yang diantisipasi tercermin dalam keputusan pembelian (Rahman & Sultana, 2022). Pemahaman yang lebih mendalam tentang preferensi konsumen terhadap sampo Pantene dan elemen-elemen yang paling mempengaruhi keputusan pembelian mereka akan diperoleh dengan mengevaluasi dampak faktor-faktor tersebut terhadap keputusan pembelian konsumen.…”
Section: Pendahuluanunclassified
“…Evaluasi individu terhadap barang dan pilihan yang dianggap paling menguntungkan dalam hal kualitas, biaya, dan keuntungan yang diantisipasi tercermin dalam keputusan pembelian (Rahman & Sultana, 2022). Pemahaman yang lebih mendalam tentang preferensi konsumen terhadap sampo Pantene dan elemen-elemen yang paling mempengaruhi keputusan pembelian mereka akan diperoleh dengan mengevaluasi dampak faktor-faktor tersebut terhadap keputusan pembelian konsumen.…”
Section: Pendahuluanunclassified
“…Ganapathi (2015) demonstrated that convenience, security, website features, and time-saving significantly drive consumers' online shopping behavior. Rahman (2015) underscored the significance of convenience and time-saving in influencing the online shopping behavior of the youth generation in Malacca. Diao (2015) distinguished that students prioritize price when shopping online, whereas others prioritize product quality, service, and security, although price remains a crucial consideration for them as well.…”
Section: Literature Reviewmentioning
confidence: 99%